Patient Surveillance After Cancer Treatment - Johnson, Frank E.; Maehara, Yoshihiko; Browman, George P.; Margenthaler, Julie A.; Audisio, Riccardo A.; Thompson, John F.; Johnson, David Y.; Earle, Craig C.; Virgo, Katherine S. (Current Clinical Oncology,, 2013)
Patient Surveillance After Cancer Treatment covers the history of cancer patient surveillance after curative-intent treatment, the rationale, the methodologies used in the past and at present, the methodologies that will probably emerge in the future, the costs of surveillance, the definitions of various terms used in the field, and how those who are interested in the topic can get more information about it from the internet. The secondary focus of the book is to publicize the need for well-designed, adequately powered randomized clinical trials comparing two (or more) surveillance strategies for each type of cancer. The audience includes all oncologists, cancer researchers, medical economists and policy makers in government and insurance companies, and finally, interested patients. This book is part of the Current Clinical Oncology series, which provides cutting-edge knowledge of cancer diagnosis, management, and treatment. World renowned experts share their insights in all the major fields of clinical oncology. From the fundamentals of pathophysiology to the latest developments in experimental and novel therapies, Current Clinical Oncology is an indispensable resource for today's practicing oncologist.